Analysis of Adolescent Consumptive Behavior: Determinants and Their Impact on Psychological Well-Being - Ari Riswanto; Fazrian Thursina; Riffalni Dela Nurlaila; Fitriana Kusuma (Westscience Press, 2023)
Consumptive behavior in adolescents is an increasing phenomenon and is becoming a concern in society. This study aims to analyze the determinants of consumptive behavior in adolescents and their impact on their psychological well-being. The determinants analyzed include internal factors such as motivation, personality, self-concept, learning process, and lifestyle, as well as external factors such as culture, social class, reference groups, and family. The impact of consumptive behavior on the psychological well-being of adolescents was the main focus of this study. Consumptive behavior can cause various problems in adolescent life, such as reducing saving opportunities, difficulty distinguishing between wants and needs, and not having an emergency fund. In addition, consumptive behavior also has an impact on self-esteem and psychological well-being of adolescents. The research method used in this study is a descriptive qualitative approach, with data collection techniques through in-depth interviews, literature studies, and observation. The results of this study are expected to provide a better understanding of the factors that influence consumptive behavior in adolescents and their impact on their psychological well-being. Furthermore, these findings could form the basis for the development of interventions and educational programs that are effective in reducing consumptive behavior and improving adolescent psychological well-being.